1990
DOI: 10.1111/j.1749-6632.1990.tb34293.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adipose Tissue Distribution on the Biological Activity of Androgensa

Abstract: To establish whether the conversion of androstenedione (A) to estrogens and 5 alpha-reduced metabolites in human adipose tissue was determined by the site of origin of the tissue, studies were carried out on adipose stromal cells from different body sites. Adipose tissue was obtained from the breast, omentum, abdomen, lower thigh, upper thigh, buttock, and flank from patients undergoing liposuction for cosmetic reasons or at surgery. Stromal cells were isolated after incubation of the adipose tissue with colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…In cultured preadipocytes derived from human subcutaneous abdominal and omental adipose tissue, the formation of androgens from androstenedione was 10-fold greater than the formation of estrone, whereas in adipose tissue from the buttock and thigh, the production of androgens and estrone from androstenedione was equivalent. 7 Consistent with this, aromatase mRNA levels were higher in the buttocks than in subcutaneous abdominal adipose tissue of women. 8 These data suggest that there are regional variations in the level of expression of aromatase and 17b-HSD in the adipose tissue of women.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In cultured preadipocytes derived from human subcutaneous abdominal and omental adipose tissue, the formation of androgens from androstenedione was 10-fold greater than the formation of estrone, whereas in adipose tissue from the buttock and thigh, the production of androgens and estrone from androstenedione was equivalent. 7 Consistent with this, aromatase mRNA levels were higher in the buttocks than in subcutaneous abdominal adipose tissue of women. 8 These data suggest that there are regional variations in the level of expression of aromatase and 17b-HSD in the adipose tissue of women.…”
Section: Introductionsupporting
confidence: 69%
“…4,5 In adipose tissue, aromatase activity and mRNA is localised predominantly in preadipocytes. 5,6 Killinger et al 7 reported that there are regional differences in preadipocyte sex steroid production. In cultured preadipocytes derived from human subcutaneous abdominal and omental adipose tissue, the formation of androgens from androstenedione was 10-fold greater than the formation of estrone, whereas in adipose tissue from the buttock and thigh, the production of androgens and estrone from androstenedione was equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…25% estrone formation. The low rates of estrone formation in these cells (Killinger et al 1990) could not have been detected using our method. Altogether, our results do not seem to be in disagreement with other previous studies regarding aromatization in adipose tissue.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, our finding of only moderate aromatase expression in such tissue samples is not surprising. Killinger et al (1990) also demonstrated that percent conversion of androstenedione to estrone ranged between 0 . 01 and 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase activity is 6-30 times higher in fat taken from the upper thigh, buttocks and flank vs the abdomen. 24,25 It is also possible that aromatase regulation varies across fat deposit locations. 26 Thus, the effect of CYP19A1 polymorphisms on obesity-related phenotypes may differ across the body.…”
Section: Discussionmentioning
confidence: 99%